Compacting Proteins: Pros and Cons of Osmolyte-Induced Folding - P. Melo, Eduardo; Estrela, Nidia; Lopes, Carlos; C. Matias, Ana; Tavares, Evandro; Ochoa-Mendes, Vanessa (Current Protein and Peptide Science, 2010)
Biomedical applications of osmolytes, including stabilization of protein-based pharmaceutics, preservation of living biological material and potential therapeutic prescription in vivo, are intimately related to the fact that osmolytes favour the native structure of proteins. The shift towards the native structure is associated to the compaction of the protein by a non-specific mechanism. This compaction is observed mostly for the unfolded state but also for the transition state ensemble and even for the native state. In addition, more stable three-dimensional structures are more stabilized by osmolytes if the overall protein fold is the same indicating that point mutations and osmolytes should share a similar mechanism for protein stabilization. A synergistic effect to increase protein stability between accumulation of osmolytes and protein engineering strategies seems to have operated during evolution. However, the conformational pre-organization of the unfolded state (compaction) induced by osmolytes which increases the folding rate, might lead to the accumulation of off-folding pathway intermediates with non-native structure that delay folding. Also, osmolytes favor protein aggregation as an alternative way to shield protein surfaces from the solvent. The sometimes observed effect of osmolytes on the prevention of protein aggregation is apparent as they only decrease the accumulation of aggregation-competent partially unfolded states.
Keywords: protein conformation